Use of psychotropic drugs before pregnancy and the risk for induced abortion: population-based register-data from Finland 1996-2006 - Ritvanen Annukka; Artama Miia; Gissler Mika; Wahlbeck Kristian (BMC, 2010)
Abstract Background Some, though not all studies have reported an increased risk for mental health problems after an induced abortion. Problems with design and data have compromised these studies and the generalisation of their results. Methods The Finnish Medication and Pregnancy database (N = 622 671 births and 114 518 induced abortions for other than fetal reasons) in 1996-2006 was utilised to study the use of psychotropic drugs in the three months before a pregnancy ending in a birth or an induced abortion. Results In total 2.1% of women with a birth and 5.1% of women with an induced abortion had used a psychotropic medicine 0-3 months before pregnancy. Psychotropic drug users terminated their pregnancies (30.9%) more often than other pregnant women (15.5%). Adjustment for background characteristics explained one third of this elevated risk, but the risk remained significantly increased among users of psychotropic medicine (OR 1.94, 95% confidence intervals 1.87-2.02). A similar risk was found for first pregnancies (30.1% vs. 18.9%; adjusted OR 1.53, 95% confidence intervals 1.42-1.65). The rate for terminating pregnancy was the highest for women using hypnotics and sedatives (35.6% for all pregnancies and 29.1% for first pregnancies), followed by antipsychotics (33.9% and 36.0%) and antidepressants (32.0% and 32.1%). Conclusions The observed increased risk for induced abortion among women with psychotropic medication highlighs the importance to acknowledge the mental health needs of women seeking an induced abortion. Further studies are needed to establish the impact of pre-existing differences in mental health on mental health outcomes of induced abortions compared to outcomes of pregnancies ending in a birth.